EFEK MENGIKUTI EKTRAKURIKULER OLAHRAGA DAN TINGKAT KEBUGARAN JASMANI TERHADAP PEMBENTUKAN SELF-ESTEEM SISWA DI SEKOLAH MENENGAH KEJURUAN (SMK) - Saputra, Wahyu (STKIP Subang, 2017)
The purpose of this study is understanding the effect of sport extracurricular activity and non sport extracurricular activity,and physical fitness level to the student?s self-esteem at SMK Cipta Skill Bandung. This study used expost facto method with casual comparative design. Population of this study is all of 150 students in total who join extracurricular in SMK Cipta Skill Bandung, and the sample using accidental sampling technique with 60 students at total. The instrument of this study is self-esteem Inventory (SEI) questionnaire to measure self-esteem score and physical fitness test Indonesia (TKJI) is used to measure physical fitness. Collected data is analized statistically using ANCOVA analizing technique sith significant range ? < 0.05. the result of processed data shows that the score of 1)self-esteem of the students who join sport ectracurycullar is better than non-sport extracurricular. 2) There is no difference of physical fitness to the self-esteem of student who join extracurrycullar. 3) the extracurricular activity and physical fitness makes impact simultaneously to the students self-esteem.